Pencerminan Gaya Kepemimpinan Transformasional Pimpinan Amal Usaha Muhammadiyah Bidang Ekonomi Syariah Di Ponorogo - Heri Wijayanto; Ninik Srijani (ITB AAS INDONESIA Surakarta, 2023)
Leadership style can be interpreted as attitudes and actions taken by leaders in dealing with subordinates, regulating an organization's operational system, carrying out and overseeing policies and solving problems both internally and externally. Transformational leadership style is reflected in the indicators: charisma, individual considerations, intellectual stimulant, and inspirational. The values of transformational leadership of the Amal Usaha Muhammadiyah (AUM) influence the success of the Muhammadiyah organization at the branch, branch, regional, regional and central levels. The purpose of this study was to determine the reflection of the values of charisma, individual considerations, intellectual stimulants, and inspirational leadership of AUM in Ponorogo, and to find out the indicators of the most dominant transformational leadership style possessed by AUM leaders. advancing AUM. The research method uses primary data, the population of all residents of Mahammadiyah in Ponorogo, with the sampling technique of cluster sampling. Analytical tool with quantitative descriptive. The number of respondents involved 100 people. Research result is, AUM employees have the perception that AUM's leadership in Ponorogo reflects a high level of transformational leadership. Charisma, inspirational, intellectual stimulant and individual considerations which are the characteristics of transformational leadership. AUM's leadership has a high rating from AUM's employees, and, based on these results, it can be concluded that the leadership style of AUM leaders throughout Ponorogo when reflected in the transformational leadership style has a high reflection